The subchronic phencyclidine rat model: relevance for the assessment of novel therapeutics for cognitive impairment associated with schizophrenia - Janhunen, Sanna (My University, 2023)
Rationale: Current treatments for schizophrenia have modest, if any, efficacy on cognitive dysfunction, creating a need for novel therapies. Their development requires predictive animal models. The N-methyl-D-aspartate (NMDA) hypothesis of schizophrenia indicates the use of NMDA antagonists, like subchronic phencyclidine (scPCP) to model cognitive dysfunction in adult animals. Objectives: The objective of this study was to assess the scPCP model by (1) reviewing published findings of scPCP-induced neurochemical changes and effects on cognitive tasks in adult rats and (2) comparing findings from a multi-site study to determine scPCP effects on standard and touchscreen cognitive tasks. Methods: Across four research sites, the effects of scPCP (typically 5 mg/kg twice daily for 7 days, followed by at least 7-day washout) in adult male Lister Hooded rats were studied on novel object recognition (NOR) with 1-h delay, acquisition and reversal learning in Morris water maze and touchscreen-based visual discrimination. Results: Literature findings showed that scPCP impaired attentional set-shifting (ASST) and NOR in several labs and induced a variety of neurochemical changes across different labs. In the multi-site study, scPCP impaired NOR, but not acquisition or reversal learning in touchscreen or water maze. Yet, this treatment regimen induced locomotor hypersensitivity to acute PCP until 13-week post-cessation. Conclusions: The multi-site study confirmed that scPCP impaired NOR and ASST only and demonstrated the reproducibility and usefulness of the touchscreen approach. Our recommendation, prior to testing novel therapeutics in the scPCP model, is to be aware that further work is required to understand the neurochemical changes and specificity of the cognitive deficits.
Keywords: Adult rat, Cognition, Schizophrenia, Subchronic phencyclidine, Touchscreen, Visual discrimination, Water maze